Pengaruh Indeks Pembangunan Manusia (IPM) Dan Pertumbuhan Usaha Kecil (Mikro) Terhadap Pertumbuhan Ekonomi Di Papua Tahun 2014-2023 - Mira Ulyati; Resti Isha Palupi; Muhammad Nur Fauzan; Muhammad Kurniawan (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
This study aims to analyze the effect of the Human Development Index and (small) business growth on economic growth in 2014-2024. The independent variable is the influence of the Human Development Index and business growth (small). And the dependent variable is economic growth. This study uses secondary data in the form of a time series, namely a time series for 10 years, namely from 2014-2024. Data obtained from BPS Indonesia. The research method is quantitative with data analysis used by researchers, namely classical assumption tests (normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests), multiple linear regression and statistical tests (determination coefficient tests (R2), t tests and F tests) using eviews-10. The results of partial regression coefficient (t-test) show that the human development index has no effect on economic growth. While Small Business Growth (Micro) Significant effect on economic growth. The results of the F test analysis show that there is a joint and significant influence of the two independent variables, namely analyzing the influence of the Human Development Index and business growth (small) on the dependent variable, namely country growth.